2018
DOI: 10.1016/j.jid.2017.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Xeroderma Pigmentosum Diagnosis Using a Flow Cytometry-Based Nucleotide Excision Repair Assay

Abstract: Dakup P, Gaddameedhi S. Impact of the circadian clock on UV-Induced DNA damage response and photocarcinogenesis. Photochem Photobiol 2017;93:296e303. Decraene D, Agostinis P, Pupe A, de Haes P, Garmyn M. Acute response of human skin to solar radiation: regulation and function of the p53 protein. J Photochem Photobiol B 2001;63: 78e83. Diffey BL, Oliver RJ, Farr PM. A portable instrument for quantifying erythema induced by ultraviolet radiation. Br J Dermatol 1984;111: 663e72. Fitzpatrick TB. The validity and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Patients with XP-V have almost a normal level of NER; therefore, unscheduled DNA synthesis (UDS) is more than 60%; however, they are deficient in TLS. Previously, we have reported that patients with XP-V are impaired in the (6-4)PP removal specifically in the S-phase (25). On the other hand, Francois Be'langer et al have reported that several melanoma cell lines present the S-phase specific repair deficiency of dipyrimidine photoproducts, especially that of (6-4)PP (26).…”
Section: Cancer Frequency and Age Of Onset Of Skin Cancer In Japanesementioning
confidence: 91%
See 2 more Smart Citations
“…Patients with XP-V have almost a normal level of NER; therefore, unscheduled DNA synthesis (UDS) is more than 60%; however, they are deficient in TLS. Previously, we have reported that patients with XP-V are impaired in the (6-4)PP removal specifically in the S-phase (25). On the other hand, Francois Be'langer et al have reported that several melanoma cell lines present the S-phase specific repair deficiency of dipyrimidine photoproducts, especially that of (6-4)PP (26).…”
Section: Cancer Frequency and Age Of Onset Of Skin Cancer In Japanesementioning
confidence: 91%
“…Patients with XP‐V have almost a normal level of NER; therefore, unscheduled DNA synthesis (UDS) is more than 60%; however, they are deficient in TLS. Previously, we have reported that patients with XP‐V are impaired in the (6‐4)PP removal specifically in the S‐phase . On the other hand, Francois Be'langer et al .…”
Section: Cancer Frequency and Age Of Onset Of Skin Cancer In Japanesementioning
confidence: 93%
See 1 more Smart Citation
“…Written, informed consent and assent, was obtained from all patients. The patients underwent multimodality assessment including clinical [ 11 ], genetic, MRI/CT imaging, neuropsychological, laboratory and electrodiagnostic evaluation. Records of deep tendon reflexes were available on most of the subjects evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Written, informed consent and assent, was obtained from all patients. The patients underwent multimodality assessment including clinical 10 , genetic, MRI, neuropsychological, laboratory and electrodiagnostic evaluation. Records of deep tendon re exes were available on most of the subjects evaluated.…”
Section: Methodsmentioning
confidence: 99%